PENGARUH LIKUIDITAS, FIRM SIZE, LEVERAGE DAN PROFITABILITAS TERHADAP CASH HOLDING - Nurul Adibah; Dirvi Surya Abbas; Hesty Ervianni Zulaecha; Imam Hidayat (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study is to determine the effect of Liquidity, Firm Size, Leverage, and Profitabilitas on Cash Holding in Basic and Chemical Industry Sector Companies listed on the Indonesia Stock Exchange. The population of this study includes all industrial companies in the Basic and Chemical Industry sectors on the Indonesia Stock Exchange for the 2018-2020 period. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis.